Peace and Unity as a Main Purpose of Islamic Da’wa: Semantic Study of the Word Da’wa in the Qur’an - Miftahus Surur; Asmuki Asmuki (Proceedings of International Conference on Da'wa and Communication, 2019)
Da’wa is a holy duty of the apostles who revealed to them by God. Afterwards, it is bequeathed to Moslem scholars that have capability and integrity. In this era many Da’was just contain humiliation and hate speech that destroy the unity and peace among the people. It shows that Da’wa has strayed far from its real meaning and purpose. Basically Da’wa aims to unite mankind unto One God, one tenet and universal values according on surah Ali Imran verse 64. Based on this reality, the author – by researching the word Da’wa in the Qur’an on semantic perspective – aims to return Da’wa back to its real meaning and main purpose. Semantic is the linguistic and philosophical study of meaning in language. “Semantic of The Qur’an” should be understood only in the sense of the Qur’ans weltanschauung or world view. To understand the meaning of the word Da’wa, the author – firstly – found the basic meaning and relational meaning, then the synchronic and the diachronic. The result is that Da’wa Islam invites people unto the one tenet that held by all the prophets and the earlier people. It is no worship except One God that called tauhid or monotheism. It is the principal point to get Da’wa back to advance that the main purpose of Da’wa is peace and the unity under tauhid tenet and universal values based on surah Ali Imran verse 64.